Analisis Metode Next-Generation Sequencing dalam Identifikasi Mutasi Genetik pada Streptoccocus pyogenes - Terra Murti Balerura; Reva Laura Purba; Juneth Jennifer Sobalel; Fitri Claudia Agathis Mahundingan; Alifah Putri Safina (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
This study is a literature review aimed at analyzing the role of whole-genome sequencing (WGS) in the genomic characterization of Streptococcus pyogenes, particularly in relation to virulence, antimicrobial resistance, and mobile genetic elements. The study is motivated by the high incidence of infections and the limitations of conventional methods in providing comprehensive genetic resolution. Data collection was conducted through a systematic search of scientific articles in indexed databases, with relevant and up-to-date publications serving as research instruments. Data analysis employed a descriptive-comparative approach to evaluate sequencing quality, depth of genetic variation detection, and the ability to identify foreign genetic elements. The results indicate that WGS using a hybrid assembly approach combining Illumina and Oxford Nanopore technologies produces complete genome sequences with high accuracy (Q30; >99.9%) and 100% sequence identity. Furthermore, this method effectively detects antimicrobial resistance genes, including msr(D), mef(A), erm(B), and tet(M), and identifies prophage regions associated with increased virulence. The findings demonstrate that WGS provides higher analytical resolution than conventional methods and has strong potential to support molecular diagnostics and epidemiological surveillance. This study contributes to improving pathogen identification accuracy and enabling integrated antimicrobial resistance monitoring